Extra-pulmonary tuberculosis frequency and the risk factors influence (case of the PHE-Batna regional unit) (2017-2022) - Benbouza, A.; Mebarki, Y.; Righi , N.; Djebaili , R.; Mansouri, O. (International Journal of Medicine, 2024)
Context: Tuberculosis is an infectious disease that is endemic in developing countries. The causal agent is Mycobacterium tuberculosis. Extra-pulmonary tuberculosis (EPTB) is receiving renewed attention due to an unexplained increase in its relative frequency. The aim of this study was to carry out a retrospective descriptive survey to assess the frequency of extra-pulmonary tuberculosis in an eastern Algeria population range.Methods: this study took place at the regional tuberculosis Batna’s Public hospitalian establishment unit; over a period of 64 months (2017-2022). 2405 files were studied through the collection of information recorded at laboratory level.Results: Out of 2405 samples, 102 were positive (4.24%). There was a clear predominance of females (64.70%) and males (35.29%), giving a sex ratio of 1.8. The age group most affected was 11 to 49. Pus was the most common specimen with a percentage of 44.12%, followed by urine (28.43%), CSF (14.70%). The incidence of extra pulmonary tuberculosis in patients in Batna’s Department and neighbouring Departments is 4.24%, with adult women being the most affected.Conclusion: Extrapulmonary tuberculosis is common and should not be neglected; it is no longer a pathology of the past but still remains relevant today.